- The poet Moazy El Nisaboury was influenced by Arab poets - comparative study - Ghazi, Amal Abdul Aziz (Arab Journal for Sciences and Research Publishing, 2019)
Comparative studies are an important field of literary studies in the Arabic language, and their importance is shown in the fact that this area shows the greatness of Arabic language and literature and its impact on everyone who deals with it. This influence was reflected in its strongest form in the nations that entered Islam in the first Islamic conquests, One of the most affected nations is the Persian nation, the Arabic language in the poets and literature of the Persians in the early Hijri centuries influenced so strongly that some poets organized in the two tongues, and enriched their poems with quotations from the Arabic literature. They were influenced by the former and contemporary Arab poets according to culture The era that was based on the glorious poet is the poet familiar with the poetry of the Arab poets and the best representative of this vulnerability poet Moazy El Nisaboury which was marked by the appearance of his hair the effect of Arab poets in his poetry clearly. I have addressed this impact with the icons of Arabic poetry from Emraa El Qays and Abu Nawas and Al-Mutanabi in the presentation of the effects of images, meanings, rhyme, weight and others, within the limits of the comparative approach belonging to the French school supported by the descriptive analytical approach to Analysis of poetic texts, Then at the end of the research introduce the findings and recommendations
Keywords: The poet Mu’zi al-Nisaburi; Arabic poetry; the influence of poets on each other